2016
DOI: 10.1111/add.13301
|View full text |Cite
|
Sign up to set email alerts
|

A micro-temporal geospatial analysis of medical marijuana dispensaries and crime in Long Beach, California

Abstract: Aims To determine whether the density of marijuana dispensaries in California, USA, in 2012-2013 was related to violent and property crimes, both locally and in adjacent areas, during a time in which local law enforcement conducted operations to reduce the number of store-front medical marijuana dispensaries. Design Data on locations of crimes and medical marijuana dispensaries as well as other covariates were collected for a sample of 333 Census block groups. . Setting Long Beach, California, USA from Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 14 publications
5
55
0
1
Order By: Relevance
“…For instance, if a new dispensary opens in a location that was previously a vacant lot or a failed business, the dispensary will bring new foot traffic and business to the area. The increase in foot traffic is an increase in "eyes on the street," which previous work suggests reduces crime in the immediate area (Chang and Jacobson 2017;Freisthler et al 2016Freisthler et al , 2017 Moreover, dispensaries are known for having high levels of security such as security guards and cameras. Reduced crime is certainly attractive to a homebuyer, and this could explain some of the observed premium of living near a dispensary.…”
Section: A Main Specification Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, if a new dispensary opens in a location that was previously a vacant lot or a failed business, the dispensary will bring new foot traffic and business to the area. The increase in foot traffic is an increase in "eyes on the street," which previous work suggests reduces crime in the immediate area (Chang and Jacobson 2017;Freisthler et al 2016Freisthler et al , 2017 Moreover, dispensaries are known for having high levels of security such as security guards and cameras. Reduced crime is certainly attractive to a homebuyer, and this could explain some of the observed premium of living near a dispensary.…”
Section: A Main Specification Resultsmentioning
confidence: 99%
“…Chang and Jacobson (2017) for example, find that localized property crime rates are likely to decrease in response to medical marijuana dispensary openings. See Freisthler et al (2016Freisthler et al ( , 2017 and Kepple and Freisthler (2012) for similar applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research showed that the availability of medical cannabis dispensaries increased its use, and problems with cannabis abuse [7,8], and was associated with increased likelihood of child physical abuse [9]. Availability of medical cannabis dispensaries was associated with increased crime in Los Angeles, California [10], while no associations were found between density of medical cannabis dispensaries and crime in Sacramento, California [11] or in Long Beach, California [12]. In Colorado, legalisation of recreational cannabis was associated with an increase in health-care utilisation due to burns, cyclic vomiting syndrome or ingestion complications [13].…”
Section: Introductionmentioning
confidence: 97%
“…Given the value of social media as a marketing strategy for businesses, we additionally examine the popularity of social media sites maintained by Weedmaps, indicated by the number of followers on each site, and the demographic characteristics of these followers on two popular social media platforms (i.e., Instagram and Twitter). Weedmaps is described as the “ first and largest global technology and media company in the marijuana space ” (Business Wire, 2016) and numerous scientific studies have utilized Weedmaps as a resource for dispensary information (Freisthler & Gruenewald, 2014; Freisthler, Ponicki, Gaidus, & Gruenewald, 2016; Mukhija & Loukaitou-Sideris, 2015). Weedmaps enables potential customers to identify marijuana retailers near their location and share customer reviews about the quality of products and services of the retailers.…”
mentioning
confidence: 99%